Biological Roles of Uterine Glands in Pregnancy - Spencer, Thomas E. (Seminars in Reproductive Medicine, 2014)
All mammalian uteri contain glands in the endometrium that synthesize or transport and secrete substances essential for survival and development of the conceptus (embryo/fetus and associated extraembryonic membranes). This review summarizes information related to the biological roles of uterine glands and their secretions in blastocyst/conceptus survival and implantation, uterine receptivity, and stromal cell decidualization in humans and animal models. The infertility and recurrent pregnancy loss observed in the ovine uterine gland knockout (UGKO) model unequivocally supports a primary role for uterine glands and, by inference, their secretions present in uterine luminal fluid in survival and development of the conceptus. Further, studies with mutant and progesterone-induced UGKO mice found that uterine glands and their secretions are required for establishment of uterine receptivity and blastocyst implantation as well as stromal cell decidualization. Similarly in humans, uterine glands and their secretory products are likely critical regulators of blastocyst implantation, uterine receptivity, and conceptus growth and development during the first trimester. Circumstantial evidence suggests that deficient glandular activity may be a causative factor in pregnancy failure and complications in humans. Thus, an increased understanding of uterine gland biology is important for diagnosis, prevention, and treatment of fertility and pregnancy problems in mammals.
Keywords: uterus; glands; blastocyst; implantation; decidualization; pregnancy